FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT PADA BANK PERKREDITAN RAKYAT (BPR) DI PROVINSI RIAU TAHUN 2006-2015 - Gift, Vhietrin; Putro, Tri Sukirno; Mayes, Anthony (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to find out how to the influence of third parties funds, interest rates, and Non Performing Loan agains the distribution of credit on the Bank of the People in Riau Province during 2006-2015. The data used in this research is the data time series from 2006 to 2015 obtained from annual data published by Bank Indonesia. The analytical method used is multiple regression analysis. Tests conducted on the hypothesis and the reliability of the data (assuming classical) using significance level of 5%. From the results of this research were obtained that the variabel of third parties funds, interest rates and Non Performing Loan simultaneously give significant effects agains the distribution of credit on the Bank of the People in Riau Province during 2006-2015 with F of 716,659 and significant level of 0,000. From the results of the t-test with significant levels of partial a = 5% is obtained that the variabel of third parties funds effect positive and significant, interest rates effect positive and insignificant and Non Performing Loan effect positive and significant agains the distribution of credit on the Bank of the People in Riau Province during 2006-2015. While third parties funds has variabel influence the more dominant agains the distribution of credit on the Bank of the People with significant levels of 0,000. Great influence posed (Adjusted R-Square) by a third variabel to the variabel dependent is 99,6%, 0,4% while the rest is affected by other variabels not examined in this research.Keywords : Distribution Of Credit, Third Parties Funds, Interest Rates, Non Performing Loan (NPL)